Table of Content - - (Journal of Educational and Psychological Sciences, 2023)
Table of Content: 1. Organizational health and its role in achieving institutional excellence in Yemeni government universities from the point of view of academic and administrative leaders for the year 2022- 2021 Mrs. Marwa Hammoud Muhammad Qadhah, Co- Prof. Abdulaziz Abdulhady Alamery 2. The Effectiveness of Integrating Augmented Reality in Education: A Review of the Literature from 2019 to 2022 Mrs. El-GHERYB Chaymae 3. The educational aspects inferred from the rights of the trustees in Islamic jurisprudence Mr. Bader Jazza Naif Alnemasi 4. The effectiveness of the use of electronic multimedia activities to develop academic skills among students of the first grade intermediate with intellectual disabilities who are capable of learning in Al-Kharj Governorate Mrs. Sara Nasser Albarrak 5. Obstacles to Vocational Rehabilitation for people with InteIIectuaI Disabilitity from The Point of View of Special education Teachers in the Secondary School in Tabuk City Mrs. Taghreed Atallah Alfaqir , Prof. Mohammed Abdullah Asiri 6. The effect of using (Posse) strategy in teaching Arabic language on development of reading comperhension skill for Basic 10th grade female students Dr. Othman Naser Mansour , Mrs. Shoug Ahmad Mustafa 7. Requirements and effectiveness of distance education in primary schools in Abha during the Corona pandemic from the point of view of educational supervisors and school leaders Prof. Mahmoud Helal Abdelkader 8. The Role of Blended Education in Developing Attitudes towards learning English language for Sixth Grade Students from The Point of view of Teachers in Jordan Mrs. Shatha Yasser Hiyasat , Prof. Odeh Abd Al- Gawad Abu Sneina